High‐dose‐rate brachytherapy and hypofractionated external beam radiotherapy combined with long‐term androgen deprivation therapy for very high‐risk prostate cancer. (7th July 2020) - Kasahara, Takashi; Ishizaki, Fumio; Kazama, Akira; Yuki, Eri; Yamana, Kazutoshi; Maruyama, Ryo; Oshikane, Tomoya; Kaidu, Motoki; Aoyama, Hidefumi; Bilim, Vladimir; Nishiyama, Tsutomu; Tomita, Yoshihiko
Abstract : Objective: To estimate the outcomes of high‐dose‐rate brachytherapy combined with hypofractionated external beam radiotherapy in prostate cancer patients classified as very high risk by the National Comprehensive Cancer Network. Methods: Between June 2009 and September 2015, 66 patients meeting the criteria for very high‐risk disease received high‐dose‐rate brachytherapy (2 fractions of 9 Gy) as a boost of external beam radiotherapy (13 fractions of 3 Gy). Androgen deprivation therapy was administered for approximately 3 years. Biochemical failure was assessed using the Phoenix definition. Results: The median follow‐up period was 53 months from the completion of radiotherapy. The 5‐year biochemical failure‐free, distant metastasis‐free, prostate cancer‐specific and overall survival rates were 88.7, 89.2, 98.5 and 97.0%, respectively. The independent contribution of each component of the very high‐risk criteria was assessed in multivariable models. Primary Gleason pattern 5 was associated with increased risks of biochemical failure ( P  = 0.017) and distant metastasis ( P  = 0.049), whereas clinical stage ≥T3b or >4 biopsy cores with Gleason score 8–10 had no significant impact on the two outcomes. Grade 3 genitourinary toxicities were observed in two (3.0%) patients, whereas no grade ≥3 gastrointestinal toxicities occurred. Conclusions: The present study shows that this multimodal approach provides potentially excellent cancer control and acceptable associated morbidity for very high‐risk disease. Patients with primary Gleason pattern 5 are at a higher risk of poor outcomes, indicating the need for more aggressive approaches in these cases.